Synthesis and Biological Evaluation of the Anti-Melanogenesis Effect of Coumaric and Caffeic Acid-Conjugated Peptides in Human Melanocytes - Park, Kyeong-Yong; Kim, Jiyeon (Frontiers in Pharmacology, 2020)
Excessive pigmentation and reduced elasticity are the major skin problems that dermatologists and cosmetologists address. Compounds that inhibit melanin production might contribute to improving skin problems. In this study, we investigated whether coumaric acid- and caffeic acid conjugated peptides might affect alpha-melanocyte stimulating hormone-induced melanin production, tyrosinase activity, and melanin synthesis-related gene expression in SK-MEL-2 human melanoma cells. Coumaric acid and caffeic acid showed no significant cytotoxicity, and they inhibited melanin production. In addition, coumaric acid- and caffeic acid conjugated peptides suppressed tyrosinase activity more than arbutin, a known tyrosinase inhibitor. Quantitative real-time PCR (qRT-PCR) results also showed that both peptides inhibited the expression of melanin synthesis-related genes, TYR, TYRP1, TYRP2, and MITF. In particular, among the nine conjugated peptides tested, caffeic acid linked to a Gly-Gly-Gly linker and conjugated to the tripeptide, ARP, showed the greatest inhibition of gene expression in the qRT-PCR analysis. These results suggested that the inhibition of melanin exerted by coumaric acid- and caffeic acid-conjugated peptides might provide important information for the development of pigmentation-related skin diseases and cosmetic products.